Opium the Best Remedy - Harold Merskey (Pain Research and Management)
Sydenham was the leading English physician of the 17th century and probably to the present time. He was using a well tried remedy. It had been known by then for about 4000 years, frequently mentioned by Hippocrates, and recognized in use in medieval Europe where it probably came through Arabic traders and was well established in use in Paris by the 12th century (2). Professional concerns up to the time of Sydenham were not about addiction. As can be seen from his text, they were about whether the drug was available in adequate preparations, whether there was any difference between opium and other narcotics, particularly comparing the natural juice with "its artificial preparations" (1) (all of which he thought to be about equal in effect), whether it was stimulant or restorative and invigorating, and whether it was being properly used for all the conditions in which it could be helpful. Addiction, dependence and insanity are not mentioned, although the fact that it could occasionally promote excitement ("frenzy") was known.